Learning Virtual Objects in Astronomy teaching: Some problem-solving proposals by Stellarium software - Longhini, Marcos Daniel (2010)
This study aims initially to discuss the use of learning virtual objects (LVO) in Education, specially, concerning Science teaching. In this context, we proposed six teaching activities planned according to the Stellarium software (version 0.10.1),which was referred by us as a LVO. These activities were proposed as problemsolving that included themes relating to Astronomy, such as solar, moon and stars positions and movements and also geographic localization.